PEUSIJUEK INDIGENOUS PSYCHOTHERAPY: Being Oneness to Nature in God’s Acceptance - Dhuhri, Saifuddin; Agustina, Linur Ficca; Fauziyah, Nurul Khansa (UIN Sumatera Utara, 2024)
This article is an attempt to respond the following two questions; what is the nature of peusijeuk and how it is related to human well-being, and how peusijeuk works as a therapy. Grounded on a critical view upon mainstream theories of psychology, this work accordingly advocate indigenous psychology by majorly comparing it to behaviourist and psycho-analysis theories and, more importantly, presents an alternative therapy for well-being, namely; Peusijeuk therapy. Quasi-experiments is the main method used to measure the work of peusijeuk as an alternative therapy, while in-depth interview procedure also employed for unearthing therapeutical competences of peusijeut and its philosophical justification. Finally, the article brings about materials used for Peusijuek and the philosophical signification, steps, and mechanisms of Peusijeuk therapy performance. Grounded in the experiment of five participants and enlightened by Islamic mysticism, such as Ibn Arabi’s teachings, I argue that many elements of nature, e.g., scent, water, soil, rice, salt, tree leaves, and trunks, have baraka, so humans can spiritually benefit from the environment, by way of performing Peusijuek ritual procedures. By doing so, they are able to attain their power/energy, which bring them happiness and improve human mental well-being.